Exploring Arab Muslim Representation in the Plays of Wajdi Mouawad, Jose Rivera, Rajiv Joseph, Jessica Blank, and Erika Jensen in American Literature: A Cultural Reflection. - Hussein, Mohammad Abed; Benny, N. Solomon (South Asian Journal of Social Sciences and Humanities, 2025)
The Western media has produced Arab Muslim identities according to political circumstances leading to simplified generalizations about this community (Said, 1978). Modern United States theatre now provides platforms for complex representations that undermine mainstream perceptions of Arab Muslims. This study analyzes how Arab Muslims are portrayed in modern theatre through a critical evaluation of Scorched. A postcolonial analysis based on Said’s Orientalism (1978) and Bhabha’s theory of hybridity (1994) helps this study explore how these theatre productions counter-simplified portrayals by presenting multifaceted representations of Arab Muslim identity. War experiences displacement and memory function as the main focus points in the analysis when using Trauma theory (Caruth, 1996) and performance studies (Schechner, 2013). The Siege depicts the Palestinian battle against occupation (Abu-Manneh, 2016). The author uses both comic elements and dreamlike qualities in Bengal Tiger at the Baghdad Zoo to portray war’s irrationality (Carlson, 2001). Aftermath uses the testimonies of Iraqi refugees to show their human side by enhancing their voice presence (Blank & Jensen, 2010). This research expands the understanding of Arab Muslim portrayal in American theatre while showing theatre as a mechanism to evaluate politics and build cross-cultural understanding (Hughes, 2016).